Narrative models and temporal dimensions - Piccinno, Marco; Fiorentino, Emanuela (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2016)
This paper reports the findings of a research aimed at validating the test on narrative models; this test was developed by M. Piccinno in 2005 with the aim of identifying the narrative model through which the person relates to himself and to others their life story. The purpose of this research is to continue in the process of validation of the constructs and test items of Piccinno, through a process of analysis focuses on three different testing procedures. The first of them, consists in the analysis factorial conducted on the results produced by the test in question on a group of 500 adolescents. The second step is to submit to the test of Cronbach the results obtained from the factor analysis. Finally, we will proceed to calculate the indices of correlation between the scores on the test items and scores of “Zimbardo Time Perspective Inventory” (1999).